2018
DOI: 10.1155/2018/1707959
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Euthyroid Graves’ Ophthalmopathy in a Patient Sero-Negative for TSH Receptor Autoantibody

Abstract: We report of a case of Graves' ophthalmopathy presented solely with symptoms of the eyes with normal thyroid function tests and negative immunoreactive TSH receptor autoantibody. 40-year-old male was referred to our hospital due to 2-month history of ocular focusing deficit without any signs or symptoms of hyper- or hypothyroidism. Serum thyroid function tests and 99mTc uptake were both within the normal range. Anti-thyroid autoantibodies were all negative except for the cell-based assay for serum TSH receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The abnormalities upon thyroid examination identified among euthyroid patients are the presence of thyroid enlargement (24-40%), low TSH (14-23%), no or low response of TSH to thyrotropin releasing hormone (TRH) stimulation (40-63%), high thyroid uptake of iodine (20%), negative TSH suppression test (30-73%), positive TgAb (11-67%), positive TBII (31-36%) and positive TSAb (43-87%) ( 29 ). Several cases with negative autoantibodies in patients with specific signs of ophthalmopathy have been reported ( 26 , 32 , 33 ). Moreover, Watanabe et al identified the presence of TSAb in 93% of cases by evaluation with a sensitive bioassay, which indicated its usefulness in the diagnosis of EGD with negative-autoantibodies.…”
Section: Clinical Characteristics Of Egdmentioning
confidence: 99%
“…The abnormalities upon thyroid examination identified among euthyroid patients are the presence of thyroid enlargement (24-40%), low TSH (14-23%), no or low response of TSH to thyrotropin releasing hormone (TRH) stimulation (40-63%), high thyroid uptake of iodine (20%), negative TSH suppression test (30-73%), positive TgAb (11-67%), positive TBII (31-36%) and positive TSAb (43-87%) ( 29 ). Several cases with negative autoantibodies in patients with specific signs of ophthalmopathy have been reported ( 26 , 32 , 33 ). Moreover, Watanabe et al identified the presence of TSAb in 93% of cases by evaluation with a sensitive bioassay, which indicated its usefulness in the diagnosis of EGD with negative-autoantibodies.…”
Section: Clinical Characteristics Of Egdmentioning
confidence: 99%